Out‐of‐season production of 17, 20β‐dihydroxypregn‐4‐en‐3‐one in the roach Rutilus rutilus. Issue 2 (1st July 2013) - Scott, A. P.; Hill, T.; Beresford, N.; Runnalls, T. J.; Sumpter, J. P.; Ellis, T.
Abstract : In this study, although the highest production of two physiologically significant progestins in teleosts [17, 20β‐dihydroxypregn‐4‐en‐3‐one (17, 20β‐P) and 17, 20β, 21‐trihydroxypregn‐4‐en‐3‐one (17, 20β, 21‐P)] was observed in the period just prior to spawning in both male and female roach Rutilus rutilus, there was also a substantial production (mean levels of 5–10 ng ml −1 in blood; and a rate of release of 5–20 ng fish −1  h −1 into the water) in males and females in the late summer and early autumn (at least 7 months prior to spawning). During this period, the ovaries were increasing rapidly in size and histological sections were dominated by oocytes in the secondary growth phase [ i.e . incorporation of vitellogenin (VTG)]. At the same time, the testes were also increasing rapidly in size and histological sections were dominated by cysts containing mainly spermatogonia type B. Measurements were also made of 11‐ketotestosterone (11‐KT) in males and 17β‐oestradiol and VTG in females. The 3 months with the highest production of 11‐KT coincided with the period that spermatozoa were present in the testes. In females, the first sign of a rise in 17β‐oestradiol concentrations coincided with the time of the first appearance of yolk globules in the oocytes (in August). The role of the progestins during the late summer and autumn has not been established.